Features of institutional and legal regulation of Islamic securities markets - Kravchuk, Nataliia; Verbitska, Mariana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article provides a comparative analysis of the principles of functioning and features of the institutional and legal regulation of the Islamic securities markets, their functional purpose in the modern geo-financial space has been revealed. The role of Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) in developing international legal standards for the global Islamic finance industry and the Sharia Advisory Council (SAC) has been described, which focuses on research and analysis of Sharia principles that can be used to introduce new financial products and instruments into the Islamic securities market. The problematic aspects of the development of the Islamic securities markets have been singled out and the necessity of creating a single Islamic stock market with unified international legal standards for its functioning has been substantiated.